EFFECTS OF THREE FEEDING FREQUENCIES ON GROWTH, FEED UTILIZATION AND SURVIVAL OF TIGER SHOVELNOSE CATFISH Pseudoplatystoma fasciatum JUVENILES - GUERRA-GRANDEZ, Franco (2009)
The tiger shovelnose catfish Pseudoplatystoma fasciatum (Linnaeus, 1766), a species widely distributed in South America, is a fish that due to its high-quality meat and fast growth, has been arising the interest of fish farmers, specially in countries like Brazil, Colombia, and Peru. The Peruvian governmental agency known as PROMPERU, has been looking for new international markets for this fish overseas, and at the same time linking efforts with other Peruvian organisms in order to develop strategies and studies that can lead to the establishment of a sustainable meat production of tiger shovelnose catfish, for international trade. One of these institutions is the Peruvian Amazon Research Institute–IIAP, which is developing a series of studies in order to generate culture technology for this catfish. The main goal of this study was to evaluate the effects of three feeding frequencies (FA2, FA4, and FA6) on the growth, feed utilization and survival of tiger shovelnose catfish (P. fasciatum) juveniles fed a pelleted diet (42% CP) during 45 days. At the end of the study, no significant differences (P>0.05) in fish growth, feed utilization and survival levels were recorded as result of the three feeding frequencies (2, 4 and 6 times/day) evaluated. To sum up, tiger shovelnose catfish juveniles of around 20 g of mean body weight would only need to be fed twice per day, which will allow the fish farmers to obtain an adequate fish yield performance with minimal work requirement.